2010
DOI: 10.3759/tropics.19.85
|View full text |Cite
|
Sign up to set email alerts
|

Ground-dwelling ant diversity in Maliau Basin, Borneo: Evaluation of hand-sorting methods to estimate ant diversity

Abstract: The ground-dwelling ant fauna in tropical forests remains the final frontier in the study of Formicidae biodiversity. This is mainly due to a lack of convenient sampling methods for the inventory of ants in soil. In the present study, employing the hand-sorting of small soil cores, we carried out the first sur vey of ground-dwelling ants in Maliau BasinConser vation Area, in Sabah, Borneo, to compare disturbed and undisturbed forest ant communities and to evaluate the sampling method , s performance in assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The change in community composition between the forest types in our study are consistent with previous studies showing lower ant diversity in logged forest 56 , 57 and genus-specific differences in tolerance to forest disturbance 38 , 54 , 93 , 94 . Differences in tolerance of ground-dwelling ants to disturbance may be mediated by microclimate variations and be contributing to variation in community composition alongside competition 67 , 79 , 95 98 , especially since ground temperatures have been reported to be higher in the logged versus primary forest areas we studied 99 .…”
Section: Discussionsupporting
confidence: 92%
“…The change in community composition between the forest types in our study are consistent with previous studies showing lower ant diversity in logged forest 56 , 57 and genus-specific differences in tolerance to forest disturbance 38 , 54 , 93 , 94 . Differences in tolerance of ground-dwelling ants to disturbance may be mediated by microclimate variations and be contributing to variation in community composition alongside competition 67 , 79 , 95 98 , especially since ground temperatures have been reported to be higher in the logged versus primary forest areas we studied 99 .…”
Section: Discussionsupporting
confidence: 92%
“…The result from soil sampling technique was lower than what has been gained through the hand collection technique in sampling this invasive species. In a previous study in Sabah, Malaysian Borneo, the soil sampling technique showed the most optimal result [19]. The hand collection was deemed to be more proactive in searching and collecting ants within the study transects compared to the other three techniques, which seemed to be more passive.…”
Section: Resultsmentioning
confidence: 81%
“…Ant samples were processed at the Animal Taxonomy Laboratory, Department of Biology, Universitas Andalas, Padang. The identification process was guided with proper references [18,19,20,21]. This process was also assisted by comparing studied specimens with curated specimens stored in the lab.…”
Section: Ant Identificationmentioning
confidence: 99%
“…Ant identification : Ant specimen was brought to the Laboratory of Animal Taxonomy at Universitas Andalas, where the identification was guided using proper references, such as Bolton (1994), Bolton (2016), andHashimoto (2003). Specimen collection in the Universitas Andalas Repository curated by the first author (Henny Herwina) was also used to assist the identification.…”
Section: Methodsmentioning
confidence: 99%